2012
DOI: 10.1007/s00134-012-2573-5
|View full text |Cite
|
Sign up to set email alerts
|

Transpulmonary thermodilution measurements are not affected by continuous veno-venous hemofiltration at high blood pump flow

Abstract: CVVH with a high blood flow pump does not alter the transpulmonary thermodilution measurements of CI, GEDVI, and EVLWI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 18 publications
2
22
0
1
Order By: Relevance
“…The calibration should be performed at least every 8 hours, or following a major change in a patient’s clinical condition [23]. To exclude variations in blood volume and temperature caused by continuous renal replacement therapy (CRRT), the calibration will not be performed immediately after CRRT is switched on or off, and the measurement can be performed after the blood temperature reaches a steady state (after two minutes) [24,25]. …”
Section: Methodsmentioning
confidence: 99%
“…The calibration should be performed at least every 8 hours, or following a major change in a patient’s clinical condition [23]. To exclude variations in blood volume and temperature caused by continuous renal replacement therapy (CRRT), the calibration will not be performed immediately after CRRT is switched on or off, and the measurement can be performed after the blood temperature reaches a steady state (after two minutes) [24,25]. …”
Section: Methodsmentioning
confidence: 99%
“…The technique cannot be used in case of extracorporeal membrane oxygenation. By contrast, continuous veno-venous haemofiltration does not affect the reliability of cardiac output measurement by TPTD [12–14], even for high blood pump flows [13]. The thermistor-tipped catheter is most often inserted in the femoral artery, but the axillary, brachial and radial (long catheter) arteries may also be used, although this requires that the elbow remains in the extended position.…”
Section: Measurement Of Cardiac Outputmentioning
confidence: 99%
“…Nevertheless, a study found that, by contrast, removing pleural effusion increased EVLW, perhaps by alleviating atelectasis in contact with the pleural effusion [67]. As for cardiac output or GEDV, renal replacement therapy [12, 13] and therapeutic hypothermia [6] do not alter the measurement of EVLW.…”
Section: Cardiac Systolic Functionmentioning
confidence: 99%
“…The measurement of CO by transpulmonary thermodilution has been demonstrated to be not only accurate but also precise [30]. The reliability is not altered in patients with renal replacement therapy, even at high blood flows [31]. The analysis of the thermodilution curve also provides other hemodynamic variables.…”
Section: Transpulmonary Thermodilutionmentioning
confidence: 98%